Methodological problems in the study of social issues: the special insight of Ruth Cardoso - Machado Pais, José (2017)
The field of Urban Anthropology in the context of Brazilian Social Sciences benefitted in great measure from the efforts and initiatives of a generation of anthropologists trained at the University of São Paulo, among which was Ruth Cardoso. This article examines the current applicability of her work, along with the genesis and influence of some of her contributions regarding the identification of new areas of study and her introduction of ground-breaking methodologies that always gave proper consideration to the traps that methodologies may bring to research.